Electric‐Potential‐Induced Complete Control of Magnetization in MnZnSb Metallic Ferromagnets. (4th December 2020) - Greve, Martin Møller; Das, Bijoy; Issac, Ibrahim; Witte, Ralf; Wang, Di; Kruk, Robert; Hahn, Horst; Dasgupta, Subho
Abstract: Magnetoelectric coupling refers to electric‐field control of magnetism, which may offer low‐power memory and beyond‐CMOS electronics. However, contenders of magnetic phase change materials, such as the dilute magnetic semiconductors (DMS), show weak ferromagnetism whereas the ultra‐small screening lengths of robust metallic magnets in artificially stacked thin film heterostructures reduce the extent of controllable magnetization to sub‐atomic distances, thereby diminishing the sheer magnitude of the tunable magnetization. In contrast, an electrochemical control of magnetization has recently been proposed where reversible electrochemistry/ion‐exchange is used to control magnetism in bulk ferromagnets. However, so far, ionic control of magnetism is limited to spinel ferrites and highly correlated oxide systems. Here, it is reported that the ionic control of magnetism can be extended to metallic ferromagnets; complete and reversible switching of ferromagnetism is demonstrated in bulk MnZnSb intermetallic compounds at room temperature. An electrochemically controlled reversible tuning of magnetization across the magnetic phase transition temperature is demonstrated. The observed phenomenon can be explained by the distortion of the crystal lattice, upon Li‐ion insertion into the MnZnSb interstitial sites, accompanied by a change in the magnetic moment of the manganese ions; acting together, both these effects lead to the collapse of the ferromagnetic order in MnZnSb. Abstract : A Li‐intercalation‐driven complete and reversible tuning of magnetization is demonstrated for a bulk volume of metallic magnet MnZnSb. The observed phenomenon can be explained either using a model of an electrochemically‐controlled reversible tuning of the magnetic transition temperature or it may also be explained by a strain‐driven destruction of the ferromagnetic ordering that leads to an antiferromagnetic state.